An Indian boy with griscelli syndrome type 2: Case report and review of literature - Ankur Singh; Amit Garg; Seema Kapoor; Nita Khurana; Miriam Entesarian; Bianca Tesi (Wolters Kluwer Medknow Publications, 2014)
Griscelli syndrome 2 is a rare autosomal recessive disorder of pigmentary dilution of hair, skin, splenohepatomegaly, pancytopenia, immune and neurologic dysfunction. Clinical course is characterized by recurrent infection triggered by uncontrolled T-lymphocyte and macrophage activation, called hemophagocytic syndrome. Since the primary presentation is with depigmented hair, we attempt to highlight diagnostic difficulties in such cases in developing countries like ours where pigmentary changes in hair and skin are commonly attributed to severe malnutrition. We also evaluated phenotype of all 10 cases of genotype (c.C550T; p.R184X), collected from published literature worldwide and emphasize the potential role of above mutation as hotspot in Southeast Asian region.